The effects on depression on the appreciation of ironic humor on physiological and subjective level - Susi, Emmi; Hölttä, Sonja (2018)
Depression has been shown to affect emotional reactivity, and thus humor appreciation can also be affected in depression. The aim of our research was to see whether such alteration occurs in appreciation of ironic humor by comparing depressed and healthy participants’ reactions to ironic conversations. With a multi-dimensional approach, we explored this on both physiological and subjective level, using skin conductance responses, facial EMG as well as subjective funniness ratings. Based on previous research, we expected the depressed and healthy participants to significantly differ in their responses to ironic humor both subjectively and physiologically. Our results show that on physiological level no group difference was found. However, based on subjective ratings, humor appreciation was altered in the depressed group, the depressed participants showing diminished humor appreciation. These controversial results support a theory that suggests a dissociation between the different domains of emotional processing in depression, specifically between autonomic responses and cognitive processes, such as emotional decision making. Understanding these underlying neural processes between humor and depression is, thus, vital in order to utilize humor more effectively in preventing and treating depression.